If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 3x + -1cos(5X) Multiply f * x fx = 3x + -1cos(5X) Remove parenthesis around (5X) fx = 3x + -1cos * 5X Reorder the terms for easier multiplication: fx = 3x + -1 * 5cos * X Multiply -1 * 5 fx = 3x + -5cos * X Multiply cos * X fx = 3x + -5cosX Reorder the terms: fx = -5cosX + 3x Solving fx = -5cosX + 3x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -5cosx-1X + 3 Simplifying f = -5cosx-1X + 3 Reorder the terms: f = 3 + -5cosx-1X
| -k+3k=15 | | 3k-7+7k=31-24k-5 | | y^2+30y+216= | | -4+5b=39 | | 8+3G=5g | | 1.4x+2.6=-8.1 | | 7(x+8)=4(x-6) | | -7(x+2)-7=-14x+7(x+4) | | 2x+5yforx=3y=9 | | 3v-7=-4v+7 | | -6s=-5s-10 | | 3(x-5)=4(x+8) | | x-14+2x+5=0 | | -u-9=-2u | | 10x-15=13x-20 | | 3(3x+9)=11x-3 | | 3y=-9+2y | | X^2-3x+2k=0 | | 13x+10=15x-16 | | -2x-3(4+5x)=-63 | | 25x^2-100x+100= | | 6m+10=8m | | 7x+4(-3x)(-12)=8 | | -10k+20=13k-18-8 | | 16(6x-24)=x-4 | | 11x-5=6x+25 | | 3g+3W=300 | | 24-4x=3(x+1) | | 65=5(4x+1) | | 7p-4+12p=-15+3p | | 8w+4=8w | | 8x^2-4x= |